Feline dermatology at Cornell University: 1407 cases (1988–2003). Issue 4 (April 2013) - Scott, Danny W; Miller, William H; Erb, Hollis N
Medical records of 1407 cats with dermatologic diagnoses made at Cornell University teaching hospital from 1988 to 2003 were tabulated. We expressed the diagnoses as counts, percentages of the cats with dermatologic disease (1407) and percentages of all cats seen at the university hospital (22, 135) during the same period. A total of 1887 diagnoses were made in the 1407 cats. We compared the age, sex and breed group of our cases with all those 22, 135 cats in ('1-by-c') χ 2 tests in which the hospital population was considered a standard (rather than a 'sample'). The 10 most common dermatoses, their counts, and the proportions of dermatologic diagnoses and of the total cat population that the cats with these dermatoses represented were: allergy (298; 15.8%; 1.35%), atopic dermatitis (194; 10.3%; 0.88%), bacterial folliculitis/furunculosis (189; 10.0%; 0.85%), otodectic mange (115; 6.1%; 0.52%), flea infestation (99; 5.2%; 0.45%), feline acne (74; 3.9%; 0.33%), flea-bite allergy (70; 3.7%; 0.32%), cutaneous adverse drug reaction (56; 3.0%; 0.25%), idiopathic eosinophilic-granuloma complex (55; 2.9%; 0.25%) and abscess (51; 2.7%; 0.23%). Allergies of all types, combined, accounted for 32.7% of all the feline dermatoses. Relative to the standard of the total hospital population, cats <2 years old and females (both intact and spayed) were significantly under-represented (all P ≤0.001) in the dermatologic case series. In contrast, Himalayans (compared with domestic short- or longhair, Persian, Siamese and other breeds) and males (both intact and neutered) were significantly over-represented (all P ≤0.001).